Desempenho e características da carcaça de tourinhos santa gertrudes confinados, recebendo dietas com alto concentrado e níveis crescentes de polpa cítrica peletizada - Henrique, Wignez; Sampaio, Alexandre Amstalden Moraes [UNESP]; Leme, Paulo Roberta; Lanna, Dante Pazzanese Duarte; Alleoni, Guilherme Fernando; Coutinho Filho, José Luiz Viana (FapUNIFESP (SciELO), 2004)
The experiment was developed to evaluate the effect of the replacement of corn grain by dehydrated citrus pulp pellets on the performance and carcass characteristics of Santa Gertrudis young bulls fed high concentrate diets. Twenty-eight bulls, with average age of nine months and an initial weight of 277 kg, were kept in individual pens and fed during 92 days, after 21 days of adaptation. The animals were fed a diet with 20% of the dry matter as corn silage, with 40% of grain. Treatments evaluated included levels of 0, 25, 40 and 55% of dehydrated citrus pulp pellets in the dry matter diet. There was no effect of citrus pulp level on the average daily gain, daily dry matter intake, feed efficiency, carcass dressing, Longissimus muscle area and the kidney, pelvic and inguinal fat. The increasing level of citrus pulp on the diet decreased linearly the backfat thickness and increased linearly the liver weight and carcass weight. The feces pH was similar for all the citrus pulp levels. Liver abscess were not detected, although the diet had high concentrate level. The dehydrated citrus pulp pellets can compound until 55% of dry matter diet, replacing corn grain to finishing young bulls fed high concentrate diets, with a small decrease in subcutaneous fat.
Feedlot performance and carcass characteristics of santa gertrudis bulls, fed high concentrate diets with increasing levels of dehydrated citrus pulp pellets
Keywords: Carcass dressing; Carcass weight gain; Empty body weight gain; Fat thickness; Feces pH; Liveweight gain; Animalia; Citrus; Zea mays